Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/mde.3119
|View full text |Cite
|
Sign up to set email alerts
|

A temporal perspective on the relationship between top management team internationalization and firms' innovativeness

Abstract: This study examines whether top management team (TMT) internationalization is positively related to firm innovativeness. Besides focusing on the accumulation of top managers' international knowledge and capabilities, we explore the influence of moderators reflecting temporal concerns at three levels: CEO age, TMT tenure, and firm age. Combining upper echelons theory with innovation literature and using a sample of large stock-listed German firms, we demonstrate that TMT internationalization can increase firm i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 179 publications
0
24
0
Order By: Relevance
“…Despite the scarcity of research, related research foci provide initial indications for top managers' role in the digital transformation, such as studies associating top managers with innovation outcomes or change processes. For example, innovation scholars found that TMTs directly influence innovation in firms by determining the firm's innovation strategy (Elenkov, Judge, & Wright, 2005; Talke, Salomo, & Kock, 2011; Talke, Salomo, & Rost, 2010) and resource commitment (Wrede & Dauth, 2020). Additionally, they recognize new business opportunities (Shepherd, Mcmullen, & Ocasio, 2016; Yukl, 2010).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the scarcity of research, related research foci provide initial indications for top managers' role in the digital transformation, such as studies associating top managers with innovation outcomes or change processes. For example, innovation scholars found that TMTs directly influence innovation in firms by determining the firm's innovation strategy (Elenkov, Judge, & Wright, 2005; Talke, Salomo, & Kock, 2011; Talke, Salomo, & Rost, 2010) and resource commitment (Wrede & Dauth, 2020). Additionally, they recognize new business opportunities (Shepherd, Mcmullen, & Ocasio, 2016; Yukl, 2010).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In fact, prior research found significant relationships between top managers and firms' commitment to the status quo (Hambrick, Geletkanycz, & Fredrickson, 1993) and corporate strategic change (Wiersema & Bantel, 1992). Besides, scholars suggest that top managers play a crucial role in firms' innovation efforts (Damanpour, 1991; Smith & Tushman, 2005; Wrede & Dauth, 2020). We assume that all these aspects represent critical elements in the digital transformation, too.…”
Section: Introductionmentioning
confidence: 99%
“…Saeed and Ziaulhaq (2019) highlight top managers' experience as the best strategy of the internationalization process. One of the most recent studies conducted by Wrede and Dauth (2020) claims that top management demographic factors significantly influence the internationalization process of firms.…”
Section: Introductionmentioning
confidence: 99%
“…Research also exhibited a positive relationship between the financial literacy of the top management and their participation in the national level projects, and they are confident and responsible (Santos, 2017). Additionally, a positive significant relationship is found between the top management team, innovation, and internationalization (Wrede & Dauth, 2020). Given these arguments, it is expected that the demographics of the top management are positively related to their participation in the projects of CPEC; therefore, our first set of the hypothesis is as follows:H1 Age of the top managers/owners is positively related to participation in CPEC.H2 Education of the top managers/owners is positively related to participation in CPEC.H3 Experience of the top managers/owners is positively related to the participation in CPEC.H4 Financial literacy of the top managers/owners is positively related to the participation in CPEC.…”
Section: Introductionmentioning
confidence: 99%
“…In theory, what is known about this topic is that executive team represents the upper echelons of a family firm, and their central role is undeniable throughout the family business literature (Dallura, 2019). As the key personnel who are responsible for and implement company strategies, the executive team controls organizational resources (Blanco-Alcántara, Díez-Esteban, & Romero-Merino, 2018), obtains market information (Michaela & Tobias, 2020), breeds entrepreneurial capabilities (Barroso-Castro, Villegas-Periñan, & Casillas-Bueno, 2016), and plays a vital role in the entire decision-making process of the enterprise. Especially in family firms, the executive team represents the foremost intersection between the family and the business (Binacci, Peruffo, Oriani, & Minichilli, 2016), and considering the interest the family has in preserving its influence (Morgan & Gomez-Mejia, 2014), the top executives on this team have significant influence on the company's results (Beckman, 2006).…”
Section: Introductionmentioning
confidence: 99%